MESOSISTEM DALAM NOVEL KANAK-KANAK TERPILIH - Junaidi, Rohayati; Tengku Mohd Ali, Tengku Intan Marlina; Mamat @ Mustaffa, Madiawati (Jurnal Pengajian Melayu (JOMAS), 2018)
This paper aims to analyze family relationships with the immediate environment of children in a children’s novel that has won the Hadiah Sastera Perdana Malaysia. Family is an important environment in influencing children’s psychological development. Therefore, the role of the family should be emphasized in the production of children novels in order to be a guide to the audience of the reader. In the context of literary works, the immediate surroundings seen are individuals who are directly connected with children. This analysis shows family relationships with other nearby environments that surround the character of children in selected children’s novels. This study applies one of the principles in Bronfenbrenner’s Ecological Theory (1979), a mesosystem for analyzing texts. The method used in this study is library method and text analysis. The findings show that family relationships with the immediate environment of children affect the psychological development of children. Family relations with the immediate environment can give birth to psychologically balanced children. This explains that families are individuals who play an important role in building an environment that helps children develop into positive individuals. In conclusion, the environment in children’s novels using the mesosystem in the Ecology Theory of Bronfenbrenner (1979) can explain the influence of the environment on children in selected children’s novels. Keywords: Theory Ecology; Mesosystem; Children’s Novel; Children’s; Family.